O olhar do design na psicose infantil: uma experiência com os livros digitais - GOMES, Anne Ramayhara Mendes (2023)
The present study approaches the experience of children diagnosed with psychosis and their use of digital books. It aims to analyze which elements of the graphic interface of a digital book influence the immersion process of children with psychosis. To achieve this goal, a literature review was conducted to understand the structure of the graphic interface of a digital book, as well as theoretical references on childhood psychosis to provide support for the research. The field research aimed to identify the elements of the graphic interface that provide immersion for child users with psychosis and to understand the User Experience (UX) when using digital books for psychotic children. The research proposes recommendations for the graphic interface of digital books for child users affected by psychosis. The state of the art delves into aspects that permeate the graphic interface of the digital book and the target audience of the research, discussing Universal Design for Learning, Information Design, Interaction Design, Sensory Design, and the social construction of books. To understand the target audience, the study involved psychiatric reform, understanding psychosis, and learning approaches. This qualitative case study used observation, interviews, field diaries, audio and video recording, and the Immersive Tendencies Questionnaire (ITQ) and Presence Questionnaire (PQ) to collect data on the degree to which the subject experiences the virtual environment. Sensory Design was specifically used to answer the research question of which elements of the graphic interface of a digital book influence the immersion process of children diagnosed with psychosis. The identification of these elements contributed to the proposal of educational tools that promote modification and transformation in the reality of children who suffer from psychological demands.